Irregular steel building structures subjected to blast loading - Coffield, Amy; Adeli, Hojjat (Journal of Civil Engineering and Management, 2015)
In seismic design, structural irregularity has been found to have a significant influence on structural response. The impact of structural irregularity on the global response of steel frame structures subjected to blast loading has not been examined. In the paper, six seismically designed steel framed structures are considered: moment resisting frames (MRF), concentrically braced frames (CBF) and eccentrically braced frames (EBF) each with geometric irregularity in the plan and with a geometric irregularity in the elevation. The blast loads are assumed to be unconfined, free air burst detonated 15 ft from one of the center columns. The structures are modeled and analyzed using the Applied Element Method, which allows the structure to be examined during and through structural failure. A plastic hinge analysis is performed as well as a comparative analysis observing roof deflection and acceleration to determine the effect of geometric irregularity under extreme blast loading conditions. Two different blast locations are examined. Conclusions of this research are a concentrically braced frame provides somewhat of a higher level of resistance to blast loading for irregular structures and geometric irregularity has an impact on the response of a structure subjected to blast loading.